Divergent mechanisms driving microbial necromass in topsoil and subsoil along an altitudinal gradient on the Loess Plateau - Yuqian Li; Xuyang Wang; Xiaoming Mou; Bin Jia; Jie Lian; Yayi Niu; Xiangwen Gong; Yuqiang Li (Geoderma)
Microbial necromass are one of the main sources of soil organic carbon (SOC) in terrestrial ecosystems. However, the characteristics of soil amino sugar accumulation and their contribution to the SOC pools across different altitudinal gradients and the influencing factors need to be further investigated. In this study, alpine grassland (AG), subalpine scrub (SS), alpine scrub (AS), and alpine meadow (AM) were selected along the altitudinal gradient in the Mt. Maxian. Soil amino sugars are used as biological markers for microbial necromass. Soil physical and chemical properties, microbial biomass, amino sugar content, and their contribution to SOC, and the driving factors of these changes were analyzed at the 0–20 cm and 20–40 cm soil layers. The results showed that: SOC, total nitrogen (TN) and total phosphorus (TP) contents significantly increased along the altitude but decreased with soil depth. Soil microbial necromass increased linearly with altitude and the microbial necromass content was higher in the topsoil than in the subsoil. Total microbial necromass of surface and subsoil contributed 40.21 % and 39.96 % of SOC, respectively, and the contribution of fungal necromass (37.45 % and 37.14 %) was significantly higher than that of bacterial necromass (2.76 % and 2.82 %). Soil microbial biomass and soil ecological stoichiometry directly affected the accumulation of soil microbial necromass, and had different effects on fungal and bacterial necromass. Microbial biomass and soil ecological stoichiometric ratio dominated the C accumulation process of bacterial and fungal residues in topsoil. In subsoil, however, soil ecological stoichiometric ratio and climate are important factors influencing C accumulation of bacterial and fungal residues. The findings of this study have important implications for predicting soil C cycling under global climate change.